2023
DOI: 10.1038/s41577-022-00821-1
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic age of the neonatal Fc receptor

Abstract: IgGs are essential soluble components of the adaptive immune response that evolved to protect the body from infection. Compared with other immunoglobulins, the role of IgGs is distinguished and enhanced by their high circulating levels, long half-life and ability to transfer from mother to offspring, properties that are conferred by interactions with neonatal Fc receptor (FcRn). FcRn binds to the Fc portion of IgGs in a pH-dependent manner and protects them from intracellular degradation. It also allows their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 245 publications
2
50
0
6
Order By: Relevance
“…While the opposite was not tested (i.e an antibody lacking FcRn interaction), data from the literature indicates that FcRn participates in the accumulation of WT IgG in the mucosa and contributes to protection upon mucosal challenge [55]. FcRn also mediates passive fetal humoral immunity by transferring IgG across the placenta [49]. Altogether, these data suggest that FcRn is a key contributor of the efficacy of bNAbs to prevent sexual HIV-1 infection and possibly maternofetal transmission.…”
Section: Neonatal Fragment Crystallizable Receptors-dependent Broadly...mentioning
confidence: 98%
See 1 more Smart Citation
“…While the opposite was not tested (i.e an antibody lacking FcRn interaction), data from the literature indicates that FcRn participates in the accumulation of WT IgG in the mucosa and contributes to protection upon mucosal challenge [55]. FcRn also mediates passive fetal humoral immunity by transferring IgG across the placenta [49]. Altogether, these data suggest that FcRn is a key contributor of the efficacy of bNAbs to prevent sexual HIV-1 infection and possibly maternofetal transmission.…”
Section: Neonatal Fragment Crystallizable Receptors-dependent Broadly...mentioning
confidence: 98%
“…In addition to FcγR, IgGs interact with the neonatal FcR (FcRN). Recognition of Fc by FcRn differs from that of FcγR by its stoichiometry (one Fc binds 2 FcRns) and its requirement for an acidic pH [49]. This latter is responsible for the most studied functions of FcRn, which is to recycle IgGs from endosomes to limit their degradation and expand their half-life.…”
Section: Neonatal Fragment Crystallizable Receptors-dependent Broadly...mentioning
confidence: 99%
“…255 The first half-life extension approach that was implemented entailed complexation of mIL-4 with an anti-mIL-4 antibody, BVD4-1D11, which significantly prolonged the activity of mIL-4, 256 due to neonatal Fc receptor (FcRn)-mediated recycling (Figure 3D). 257 Various groups have used this IL-4/anti-IL-4 antibody complex, termed IL-4C, as a tool to investigate fundamental IL-4 biology, 248,[258][259][260][261] as well as to translate IL-4 into a more therapeutically relevant form for treating arthritis, promoting wound healing, and inhibiting tumor formation. 197,[262][263][264] As an alternative approach for half-life extension, mIL-4 was fused to mouse serum albumin (MSA), a large, endogenous protein that is also recycled through FcRn thus extending its persistence in the bloodstream (Figure 3D).…”
Section: Rationalengineeringofil-4andil-13mentioning
confidence: 99%
“…In male ejaculate, there is between 16 and 33 μg mL −1 of IgG (depending on the volume) 8 that is secreted by B cells into the circulation and is transcytosed into the mucosal lumen by the epididymis, prostate and accessory organs of the male reproductive tract 8 . Until relatively recently delivery of IgG into the lumen was thought to be mediated by passive flux, it is now suggested that IgG is transported across epithelial cell barriers into the mucosa of mammals by FcRn 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…8 Until relatively recently delivery of IgG into the lumen was thought to be mediated by passive flux, it is now suggested that IgG is transported across epithelial cell barriers into the mucosa of mammals by FcRn. 9,10 The FcRn is expressed throughout the mammalian body on a diverse range of cell lineages, for example, epithelia, endothelia, hepatocytes, podocytes, syncytiotrophoblasts, neutrophils and antigen-presenting cells. 9 FcRn facilitates passive immunity in embryos/neonates via delivery of maternal IgG to the offspring across the placenta and from breastmilk in the neonatal GIT.…”
Section: Introductionmentioning
confidence: 99%